Waterlogging Stability Identification: Ray-Based Model Application in Mining Areas with High Groundwater Levels—A Case Study of Huainan Coal Field - Yueming Sun; Yanling Zhao; He Ren; Zhibin Li; Yanjie Tang (Land)
Surface subsidence and water accumulation are common consequences of underground coal mining in areas with high groundwater levels, leading to waterlogged zones. Predicting the stability of these subsidence-induced water bodies is critical for effective land reclamation, yet current methods remain inadequate, particularly when mining data are limited. This study addresses this gap by introducing a new approach to evaluate the stability of subsidence waterlogging zones. We developed a novel method based on the ray model to assess waterlogging stability in coal mining areas. Rays were cast from origins at 1° intervals to measure changes in water accumulation boundaries over time, using metrics like the Expansion Ratio Index and stability duration. The proposed method was applied to the Huainan coal field, a typical mining area with high groundwater levels in China. We studied 41 subsidence water patches, selecting ray origins for each patch and constructing a total of 14,760 rays at 1° intervals. (2) Out of all effective rays, 4250 (32.6%) were identified as stable. (3) Stability analysis classified 32.6% as “stable”, 66.4% as “observation required”, and 1.6% as “expanding.” Specific reclamation suggestions include filling shallow stable areas and developing permanent projects in larger stable zones.